Toward a Public Theology of Climate Change : A Chinese Perspective - Mok, Bryan, (Political and Public Theologies ;, 2026)
How can theology shape public discourse on climate change? This book explores the urgent intersection of climate justice, public theology, and environmental communication from a Chinese Christian perspective. As the world grapples with climate apocalypse, this study reveals how religious discourse can influence public opinion and policymaking. Engaging with global and Chinese contexts, it evaluates competing theological approaches and proposes a framework for a public theology of climate change. With insights into environmental activism, political deliberation, and ethical responsibility, this book equips theologians, religious scholars, and climate activists to rethink the role of religion in the fight against climate change.